Exploring the Effect of Immigration on Consumer Prices in Spain - Marcel Smolka (CESifo GmbH, 2024)
We investigate the effect of immigration on consumer prices in Spain between 1997 and 2013. Using variation across provinces, we first document a positive correlation between consumer prices and the share of migrants in the population. However, controlling for regional supply and demand shocks, and addressing endogeneity through an instrumental variables approach, we show that immigration has actually reduced consumer prices in Spain. An increase in the share of migrants by 10 percentage points reduces (CPI-weighted) consumer prices by approx. 1.25 percent. We show that the effect materializes around the years of the 2008 financial crisis, and that it is concentrated among non-tradable goods and services. Focusing on individual products, we find that some of those products that rely most heavily on migrant labor have been subject to considerable price reductions, while we find no such effects for those products that make intensive use of native labor. Finally, we find that it is immigration from outside Western Europe that led to a reduction in consumer prices, while the effect of immigration from Western Europe is zero. Overall, our results paint a complex picture of the effects of immigration on consumer prices. They support the idea that immigration can reduce consumer prices through both supply-side and demand-side channels.
Keywords: F22; J61; 330; immigration; consumer prices; Spain